Joel Sternfeld and Linda Connor. A gender perspective on landscape photography in the United States during the 1970s decade (ASRI. Art and Society. Journal for Research in Arts and Digital Humanities, 2022)
Are there differences between men and women in the way they photograph landscape? Can we find gender matters subsiding, a cultural way of seeing under those differences? Is it the gender, performative and social, something with the power to shape how we look at landscape?Based on these questions, this article analyzes the cases of Joel Sternfeld and Linda Connor, both American photographers who portrait their country in the 70s. They were both surrounded by the New Topographics movement, but not taking part of them, during a time without globalization and internet. We are in a moment where no-places began, abandoned architectures, a new understanding of the land already Occidentalized. The critical analysis of their productions during that time is focused on questions about how the way we look impose qualities to the landscape as classification, control, maintenance strategies of the hierarchy. Photography, as a tool extremely close to the power -yet maybe with ability to undermine it-, is used on landscape, which a construction itself.
Keywords: Photography; landscape; gender; nature